STUDI EVALUASI KINERJA SISTEM INTERLOCK KOMPRESOR UDARA 101-J DI PUSRI-IB BERBASIS TEKNIK PETRI NET - Sulaiman, Moh.Hamni
Air Compressor 101-J supplies process air as one of ammonia raw matterials at ammonia plant of Pusri-IB. Interlock system that is deployed in electromechanical relays circuit protects the compressor from unsafe operation conditions. When there is an unsafe operation condition, interlock system will stop the compressor in safe sequences. However, failure of interlock components (electromechanical relays) will also lead to compressor shutdown. This unexpected shutdown causes financial losses due to production stoppage. Furthermore, there is no process air supplied to ammonia plant after the compressor shutdown. This research is conducted to evaluate and improve performance of Air Compressor 101-J interlock system. Petri net is employed as analytical tool to evaluate performance of Air Compressor 101-J interlock system. Petri net describes distribution and redistribution of energy in the system in a transparent manner. System performance can be analyzed from Petri net's properties such as teachability, boundedness, and liveness. From this Petri net model, Air Compressor 101-J interlock system can be analyzed to obtain possible ways of improvement or to develop the system for better performances. The results of the Petri net analysis show that Air Compressor 101-J interlock system has no fail-safe mechanism. Failure of interlock component (relay) causes the interlock system to works, and results in compressor shutdown. A design of redundant relays configuration is proposed to solve the problem. The analysis results of the proposed redundant relays configuration show that the modified interlock system will not cause compressor shutdown, when one of the relays in this configuration fails. In other words, the modified interlock system obtains a fail-safe mechanism.